2014
DOI: 10.1071/bt14077
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy-breaking and germination requirements for seeds of Acacia papyrocarpa, Acacia oswaldii and Senna artemisioides ssp.×coriacea, three Australian arid-zone Fabaceae species

Abstract: Physical dormancy is common in seeds of arid-land legumes. Improved understanding of germination requirements of hard-seeded species will further our understanding of arid lands and aid restoration projects. We studied the germination responses of Acacia papyrocarpa (Benth.), A. oswaldii (F.Muell) and Senna artemisioides (Gaudich. ex DC.) Randell ssp. × coriacea (Benth.) Randell from a chenopod shrubland in South Australia. Imbibition testing indicated that all three species had physical dormancy, but the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…Likewise, Pound et al . (2014) found that non-treated seeds of A. oswaldii had a gradual and ongoing germination response over time and in the present study some lenses of this species popped from just being on a moistened paper towel. As noted in Burrows et al .…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Likewise, Pound et al . (2014) found that non-treated seeds of A. oswaldii had a gradual and ongoing germination response over time and in the present study some lenses of this species popped from just being on a moistened paper towel. As noted in Burrows et al .…”
Section: Discussionsupporting
confidence: 58%
“…Some studies of Caesalpinioideae and Mimosoideae species have related palisade thickness to water impermeability (e.g. Venier et al ., 2012; Pound et al ., 2014). The present study, in combination with Burrows et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various artificial techniques have been used to successfully overcome physical dormancy in legumes such as acacia species. Some studies have shown that the highest germination percentages are obtained when seeds are submerged in boiling water before being planted (Walters et al, 2004;Rasebeka et al, 2014;Pound et al, 2014). Another practice that has been applied with good results in some crops (including maize) to increase germination is soaking the seeds for 10-25h in water, (Harris et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Physical dormancy is the water impermeability of seed coats and it has been suggested that variations in the seed coat structure among neotropical Acacia species could be related to different regenerative responses to environmental conditions (Venier et al, 2014). Overall, information on seed dormancy of arid zone species is limited and particularly based on Oceania's arid zone (Pound et al, 2014).…”
Section: Introductionmentioning
confidence: 99%